Road Transportation Model for Quartermaster Distribution of Royal Thai Air Force - Khampoung, Nattaporn; Suthiwartnarueput, Kamonchanok (Journal of Applied Research on Science and Technology (JARST), 2019)
The aim of this research to study road transportation model for quartermaster distribution of Royal Thai Air Force and to compare road transportation model Milk Run transportation through every unit in the region, Milk Run transportation is divided into several routes in each region, Cross Docking Transportation and Cross Docking with Milk Run. To find alternatives that are appropriate for the distribution of supplies to each region. By using the parcel transport statistics for the fiscal year 2016-2017. Implementing the Geographic Information System (GIS) program to assist in the analysis of proper positioning for use as a distribution center for each region. Including the use of the optimal solution to support Milk Run for transport the parcels in each region. The study found that Cross Docking with Milk Run making transporting in The Northern region the lowest cost by the Department of Transport (Don Mueang) use a 10 tons truck to transport to Wing 46 as a distribution center and then let Wing 4 and the Phu Man Khao Report Station use 3 tons of truck to pick up the parcels at Wing 46. For the remaining units in the northern region, Wing 46 will use 4 tons truck delivered in Milk Run divided into 2 routes are Wing 46-Wing 41-Inthanon report station-Wing 46 and Wing 46-Air squadron 416-Air squadron 466-Wing 46 which can reduce transportation costs 18.11%, Northeastern region, Milk Run transportation is divided into several routes in each region Causing the lowest cost of transportation by the Department of Transport (Don Mueang) use a 10 tons truck to transport to Wing 23 as a distribution center. And then let Wing 23 take 4 tons of truck to deliver the package in Milk Run divided into 3 routes are Wing 23-Wing 1-Khao Phanom Rung report station-Wing 23, Wing 23-Wing 21-Phu Sing report station-Wing 23 and Wing 23- Phu Khiew report station-Air squadron 236-Air squadron 238-Air squadron 237-Wing 23 which can reduce transportation costs 2.04%. Southern region Cross Docking makes the lowest cost by the Department of Transport (Don Mueang) use a 10 tons truck to transport to Wing 7 as a distribution center. Then let the units in the north used 3 tons truck to pick up the parcels at Wing 7. It will reduce transportation costs 27.79%. the Central, Eastern and Western region transporting the parcels in the original (Direct Shipment) has the lowest transportation costs.